PENGARUH NILAI TUKAR RUPIAH , TINGKAT SUKU BUNGA DAN INFLASI TERHADAP IHSG PERIODE 2020-2023 - Imroatul Firdausiyah; Mei Indrawati; Rusdiyanto Rusdiyanto (Politeknik Bisnis Indonesia, 2024)
This study aims to investigate the impact of the rupiah exchange rate, interest rate, and inflation variables on the Composite Stock Price Index (IHSG) during the period of 2020-2023. The data utilized in this study are secondary data. The sample size used in the study comprised 48. The data analysis method employed was multiple linear regression analysis. The research findings indicate that collectively, the rupiah exchange rate, interest rates, and inflation significantly influence the Composite Stock Price Index (IHSG). Partially, it is evident that the rupiah exchange rate and inflation significantly affect the Composite Stock Price Index (IHSG), whereas interest rates do not impact the Composite Stock Price Index (IHSG).